A comparative study of twill weave reinforced composites under tension–tension fatigue loading: Experiments and meso-modelling. (January 2016) - Xu, J.; Lomov, S.V.; Verpoest, I.; Daggumati, S.; Van Paepegem, W.; Degrieck, J.
Abstract: The tension–tension fatigue characteristics of two types of twill weave carbon/epoxy composite materials have been experimentally investigated. The fatigue strain vs load cycle number is calculated with the help of digital image correlation (DIC). The increase of displacement amplitude and the degradation of the fatigue moduli for these two materials are studied and compared. The fatigue strengths obtained from fatigue tests are used to compare with those predicted by the model and good agreements are obtained. The stress fields from meso-scale FE models are used to analyse the stress concentration that leads to the fibre rupture in the warp tows.